Dexmedetomidine for modified electroconvulsive therapy: a dose-optimized treatment study - Jun Shen; Min Zhou; Guangliang Zhu; Yu Zhang; Jinzhi Ma; Dekui Li; Lei Chen; Kejun Qi; Anjiang Wang; Yang Jiang; Zhiming Dai; Xiaoming Li (European Journal of Medical Research)
Abstract Objectives To determine the optimal dexmedetomidine dose for hemodynamic stability and recovery quality in modified electroconvulsive therapy (MECT). Methods In this randomized trial, 252 patients receiving MECT were allocated to six groups (placebo, D1–D5; 42/group). Groups D1–D5 received dexmedetomidine (0.2–1.0 μg/kg) 10 min pre-anesthesia, while controls received saline. Hemodynamic parameters heart rate (HR), mean arterial pressure (MAP), seizure duration, propofol requirements, recovery times, and adverse events were analyzed. Results Doses ≥ 0.4 μg/kg (D2–D5) significantly reduced HR and MAP versus control (P < 0.05), with prolonged recovery in D4–D5 (P < 0.05). Seizure duration remained unchanged across groups. Propofol use decreased dose-dependently (D2–D5, P < 0.05). The D2 group (0.4 μg/kg) achieved optimal hemodynamic stability without excessive recovery delays. Conclusions Dexmedetomidine pretreatment at 0.4 μg/kg optimizes MECT anesthesia by balancing hemodynamic control, reduced propofol use, and rapid recovery, establishing it as the recommended dose.